2020
DOI: 10.3390/ijerph17186733
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of the Resonance Frequency Analysis Values in New Prototype Transepithelial Abutments: A Prospective Clinical Study

Abstract: Resonance frequency analysis (RFA) requires abutment disconnection to monitor implant stability. To overcome this limitation, an experimental transepithelial abutment was designed to allow a SmartPeg to be screwed onto it, in order to determine the prototype abutments repeatability and reproducibility using Osstell ISQ and to assess whether implant length and diameter have an influence on the reliability of these measurements. RFA was conducted with a SmartPeg screwed directly into the implant and onto experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…Therefore, the issue of choosing methods for determining the possibility of immediate or long-term load on the selected type of implants that will ensure the predictable result of their long-term functionality remains relevant. Such indicators are the results of the resonance frequency analysis [8], which perfectly characterizes the stability of even ultrashort implants at all stages of their osseointegration and postosseointegration periods [2], as described in this study.…”
Section: Introductionmentioning
confidence: 79%
“…Therefore, the issue of choosing methods for determining the possibility of immediate or long-term load on the selected type of implants that will ensure the predictable result of their long-term functionality remains relevant. Such indicators are the results of the resonance frequency analysis [8], which perfectly characterizes the stability of even ultrashort implants at all stages of their osseointegration and postosseointegration periods [2], as described in this study.…”
Section: Introductionmentioning
confidence: 79%
“…have suggested that removal torque measurement might not be the best test for evaluating osseointegration or the amount of bone around the implant ( 20 ). RFA, on the other hand, is a more direct measurement of the implant stability with reproducible results and independent of the implant type used ( 21 - 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Other authors used this method to assess, for example, whether the height of the abutment could influence the stability values, and the results showed that the values may vary with the increase in the abutment height [27]. However, other studies have shown that varying the height of the abutments does not change the values measured by Osstell [28,29]. In our study, abutments of similar heights were used, with a difference of 1 mm between the abutments in group A and the abutments in groups B and C. However, when straight abutments were compared with angled abutments, angled abutments had lower stability values measured by RFA [27], corroborating our results.…”
Section: Plos Onementioning
confidence: 99%